2007
DOI: 10.1038/sj.leu.2404540
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinase-1 promotes hematopoietic differentiation via caspase-3 upstream the MEKK1/MEK6/p38α pathway

Abstract: Besides its matrix metalloproteinases inhibitory activity, TIMP-1 exhibits other biological activities such as cell survival and proliferation. The intracellular signalling pathway elicited by TIMP-1 begins to be elucidated. We have shown previously that the caspase-3 and the p38a MAP kinase were activated during TIMP-1-induced UT-7 cells erythroid differentiation. In this study, we demonstrated that TIMP-1 differentiating effect can be extended to the IL-3-dependent myeloid murine 32D cell line and human eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…In the hematopoietic system, TIMP-1 was initially found to enhance the proliferation of erythroid cells and promote hematopoietic differentiation [18,39,40]. More recently, we found that TIMP-1 À/À mice present a consistent decrease in BM cellularity, including LT-HSC numbers, but no alterations in the respective percentages of circulating myeloid cells, B lymphocytes, or T lymphocytes.…”
Section: Q9mentioning
confidence: 76%
“…In the hematopoietic system, TIMP-1 was initially found to enhance the proliferation of erythroid cells and promote hematopoietic differentiation [18,39,40]. More recently, we found that TIMP-1 À/À mice present a consistent decrease in BM cellularity, including LT-HSC numbers, but no alterations in the respective percentages of circulating myeloid cells, B lymphocytes, or T lymphocytes.…”
Section: Q9mentioning
confidence: 76%
“…The inhibition of TIMP-1 expression in hMSCs significantly promoted cell growth and differentiation into adult cells of the osteogenic lineage, indicating that TIMP-1 is an endogenous attenuator of these processes. Previous reports have shown that TIMP-1 inhibits epithelial cell proliferation and osteoblastic differentiation (23,24) but stimulates differentiation in hematopoietic progenitor cells, B cells, and Burkitt lymphoma cells (25)(26)(27). However, none of these studies has provided information regarding the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3, a key regulator y protease from which many signaling pathways merge for the execution of apoptosis, participates in apoptosis induced by bcl-2/ bax, p38 and JAK-STAT [19,20] . We detected the caspase-3 expression in HepG2 cells after treatment with PE.…”
Section: Involvement Of Caspase-3 In Hepg2 Cell Apoptosis Induced By Pementioning
confidence: 99%